Bilateral facial nerve palsies due to leptomeningeal progression of lung adenocarcinoma and response to osimertinib. Issue 5 (26th May 2021) - Durie, Matthew; Faragher, Mark
Abstract : A 39-year-old female Chinese non-smoker was diagnosed with epidermal growth factor receptor mutation-positive lung adenocarcinoma with cerebral metastases and commenced erlotinib. After 5 weeks, she presented with a 3-day history of severe bilateral facial weakness (House-Brackmann grade V/VI) and hypogeusia consistent with bilateral facial nerve palsies. MRI demonstrated new, symmetrical contrast-enhancing foci at the expected location of the facial nerves, consistent with leptomeningeal progression. Erlotinib was ceased and osimertinib was commenced. Facial nerve motor and sensory function began to improve within 1 week and by 2 weeks had returned to near normal. Review at 2 and 6 months demonstrated normal facial nerve function and progressive resolution of the facial nerve lesions on MRI. While rare, leptomeningeal malignancy may present as simultaneous bilateral facial nerve palsies. Osimertinib has superior central nervous system penetration and in this case was associated with rapid and sustained clinical and radiographical resolution of the facial nerve lesions.